INDEKS KEPUASAN MASYARAKAT PENGGUNA JASA PELAYANAN KESEHATAN UPT. UNEJ MEDICAL CENTER (UMC) UNIVERSITAS JEMBER TAHUN 2007 - Khoiri, Abu; Nuryadi, Nuryadi; Anjarsari, Alice (IKESMA, 2009)
UPT. UNEJ Medical Center (UMC) is one of the health service provider institutions in Jember. Patient satisfaction is one indicator of the quality of services provided by health providers. Patient satisfaction is also an investment to get more patients and have a high loyalty. Therefore UPT. UMC requires the satisfaction index to identify the extent service user satisfaction levels of services. Community satisfaction index consisting of 14 essential elements which valid and reliable as the minimum elements that must exist. The purpose of this study was to describe the user community satisfaction index of health services in UPT. UMC. Design research using observational studies because they did not give a treatment of the respondent. While time-based research using cross-sectional approach. Respondents research were patients of UPT. UMC as many as 94 people. Results obtained research data and information that the community satisfaction index of UPT. UMC was 68.72 which included in a good performance category. Keywords : Community Satisfaction Index, Health Services, UPT. UMC.